Kemampuan Menulis Teks Laporan Hasil Observasi pada Kelas VIII SMP Negeri 7 Kota Bengkulu - Khairani, Nabilla; Wulandari, Catur; Afrodita, Meli (UNIB Press, 2025)
The purpose of this study was to determine the ability to write observation report texts in class VIII students of SMP Negeri 7 Bengkulu City. This study used a descriptive method with aquantitative approach. The population in this study were 211 students of class VIII B SMPNegeri 7 Bengkulu City. The sample in this study used purposive sampling, namely 14% ofthe total population, namely 30 students. The data collection technique used a test technique,namely students were given the task of writing an observation report text with a timeallocation of 60 minutes. The ability to write an observation report text was assessed from 3 aspects, namely, general definitions, part definitions, and conclusions. The data analysistechnique used in this study was simple statistics by calculating the average value. The results of this study indicate that the average value of the ability to write observation report texts in class VIII students of SMP Negeri Bengkulu City was 57.64 with a sufficient category. The average value of the ability to write observation report texts based on the general definition aspect is 15.85 with a sufficient category where students can write general descriptions but not in detail or completely only contain the definition of the object is not explained in more detail, the average ability to write observation report texts in students based on the definition aspect of the part is 25.85 with a sufficient category where students have written descriptions of parts but many students do not really describe the object specifically so that the description of the part is less in-depth, the average ability to write observation report texts in students based on the definition aspect of benefits/Conclusions is 15.92 with a sufficient category where students have written conclusions but students have not really understood what the conclusions are so that many conclusions made only repeat words in the general description and also do not match the objects observed. This study sees that students' writing abilities in observation report texts must be studied better so that students can really understand the structural parts in the observation report text.